Contribution of Ad-din Micro-credit program in Fistula Prevention, Case identification and Referral - Haque, Fazlul; Mohiuddin, Sheikh; Huda, Sk Nazmul (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: The objective of this presentation is to describe the practice of fistula case identification, referral and rehabilitation of patients under the Ad-din microcredit program and to share performance data and program experience in this field. Methods: Using a 4 question checklists developed through the Fistula Care Plus project, Ad-din field workers identify fistula clients from community. Ad-din does a customized rehabilitation need assessment of individual fistula cases then and supports them accordingly. Results: During this period, 358 cases have been identified with probable fistula symptoms. Diagnosis was confirmed among 169 cases through community fistula diagnosis events. Ad-din facilitated treatment of 153 cases. The program has provided rehabilitation training to 46 cases and livelihood support to 59 cases. Conclusion: Microcredit networks can be used for community-based fistula case identification, treatment facilitation, case referral and case rehabilitation. If the networks of microcredit systems in many settings are utilized in fistula prevention and care, they could be useful partners to address fistula in any community.